2018
DOI: 10.1002/2017jg004343
|View full text |Cite
|
Sign up to set email alerts
|

Selective Leaching of Dissolved Organic Matter From Alpine Permafrost Soils on the Qinghai‐Tibetan Plateau

Abstract: Ongoing global temperature rise has caused significant thaw and degradation of permafrost soils on the Qinghai‐Tibetan Plateau (QTP). Leaching of organic matter from permafrost soils to aquatic systems is highly complex and difficult to reproduce in a laboratory setting. We collected samples from natural seeps of active and permafrost layers in an alpine swamp meadow on the QTP to shed light on the composition of mobilized dissolved organic matter (DOM) by combining optical measurements, ultrahigh‐resolution F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 62 publications
(96 reference statements)
1
24
0
Order By: Relevance
“…Moreover, the filters for samples in this region were in yellow due to the high loading of soil dust. The average a CDOM (280) was the highest among all five regions (2.30 ± 0.52 m −1 ), and the S 275−295 fell in the range of 0.0170-0.0212 nm −1 (0.0188 ± 0.0015 nm −1 ), which shows similar values of leaching for permafrost on the Tibetan Plateau (Wang et al, 2018).…”
Section: Air Mass Backward Trajectories and Active-fire Datamentioning
confidence: 63%
“…Moreover, the filters for samples in this region were in yellow due to the high loading of soil dust. The average a CDOM (280) was the highest among all five regions (2.30 ± 0.52 m −1 ), and the S 275−295 fell in the range of 0.0170-0.0212 nm −1 (0.0188 ± 0.0015 nm −1 ), which shows similar values of leaching for permafrost on the Tibetan Plateau (Wang et al, 2018).…”
Section: Air Mass Backward Trajectories and Active-fire Datamentioning
confidence: 63%
“…5). This difference is likely attributed to the selective release of aromatic components from AL and carbohy- drate/protein components from the deep PL during the soil thawing process, which was observed in our previous study (Wang et al, 2018). Since chemical composition impacts the reactivity of DOM (Kellerman et al, 2015), the differing chemical composition between the AL and PL leachates that enter the stream may influence bioavailability (Vonk et al, 2013) and photolability (Stubbins et al, 2017).…”
Section: Al Leachates As a Major Source Of Stream Dommentioning
confidence: 76%
“…3850 m above sea level; m a.s.l. ); detailed description on the collapse can be found in Wang et al (2018). The top 60 cm is AL that comprises abundant grass litter and roots, underlain by dark PL without visible plant debris.…”
Section: Study Area and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, DOC released from permafrost soils contains large amounts of low‐molecular‐weight, ancient organic acids and other labile C fractions, which can be rapidly mineralized on daily to weekly time scales (Drake et al, ; Vonk et al, ; Wang, Spencer et al, ). Permafrost‐released DOC would then suffer from substantial biodegradation and release greenhouse gases before reaching nearby aquatic systems (Spencer et al, ), with DOC leached from permafrost soils having higher biodegradability than that from nearby streams or rivers (Mann et al, ; Wang, Xu et al, ). In addition to the lack of DOC observations from permafrost soils, previous studies also revealed conflicting evidence about the relative biodegradability of permafrost‐derived DOC versus DOC from active‐layer overlying permafrost.…”
Section: Introductionmentioning
confidence: 99%